Broadband local loops for high-speed Internet access - Gagnaire, Maurice (Artech House telecommunications library., 2003)
If you are a an engineer working for a telecommunications carrier or Internet service provider, or a manufacturer or student interested in communication technology and digital communications, this comprehensive overview of broadband access technologies is essential reading for you. The book offers you an in-depth understanding of unbundling for voice and data services, and provides expert guidance on hardware considerations and critical communication protocols.